COMPARATIVE EVALUATION OF CONVENTIONAL AND NEW BIOMARKERS OF RENAL INVOLVEMENT IN PATIENTS WITH TYPE 2 DIABETES MELLITUS AND HYPERTENSION – A PILOT STUDY. - RIJU MATHEW; VINITHA R. PAI; VIJAYAKUMAR. T (International Journal of Pharma and Bio Sciences, 2013)
Transient kidney damage is identified in type-2 Diabetes Mellitus(DM) and Hypertension(HT). Most of the Indian studies that evaluate the association between renal damage and DM and HT were carried out with the conventional markers. In this study renal involvement in patients with DM, HT and both were assessed by conventional biomarkers (urea, creatinine, uricacid, urine protein-creatinine ratio(PC-Ratio) and compared with newer markers (cystatinC and microalbuminuria). Results of 41 patients are compared with 19 age and sex matched controls. Among the conventional markers creatinine and PC-ratio were found to be better markers than urea. Creatinine based estimated glomerular filtration rate(eGFR) was unable to predict the early renal dysfunction. Among new markers cystatinC, microalbuminuria and cystatinC based eGFR were found to be more reliable as predictive markers. So from this study it can be concluded that the newer markers are better to assess the early renal damage in HT and in DM.